2010
DOI: 10.3390/molecules15117961
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Metabolites from the Endophytic Fungus Pichia guilliermondii Isolated from Paris polyphylla var. yunnanensis

Abstract: Three steroids and one nordammarane triterpenoid were isolated for the first time from the endophytic fungus Pichia guilliermondii Ppf9 derived from the medicinal plant Paris polyphylla var. yunnanensis. By means of physicochemical and spectrometric analysis, they were identified as ergosta-5,7,22-trienol (1), 5α,8α-epidioxyergosta-6,22-dien-3β-ol (2), ergosta-7,22-dien-3β,5α,6β-triol (3), and helvolic acid (4). Both micro-dilution-colorimetric and spore germination assays were employed to evaluate their antim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
72
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(74 citation statements)
references
References 30 publications
2
72
0
Order By: Relevance
“…The biodegradation of a mixture of pentachlorophenol (PCP), 2-chlorophenol (2-CP), 2,4-dichlorophenol (2,4-DCP), and 2,4,6-trichlorophenol (2,4,6-TCP) using fungal laccases produced by Trametes pubescens was evaluated by Gaitan et al (2011). Laccases are also able to metabolize dichlorodiphenyltrichloroethane (DDT) in soil (Zhao et al 2010) and biodegrade 2,4-dichlorophenol (Bhattacharya et al 2009). …”
Section: Bioremediation Of the Environment And Detoxification Of Efflmentioning
confidence: 99%
“…The biodegradation of a mixture of pentachlorophenol (PCP), 2-chlorophenol (2-CP), 2,4-dichlorophenol (2,4-DCP), and 2,4,6-trichlorophenol (2,4,6-TCP) using fungal laccases produced by Trametes pubescens was evaluated by Gaitan et al (2011). Laccases are also able to metabolize dichlorodiphenyltrichloroethane (DDT) in soil (Zhao et al 2010) and biodegrade 2,4-dichlorophenol (Bhattacharya et al 2009). …”
Section: Bioremediation Of the Environment And Detoxification Of Efflmentioning
confidence: 99%
“…Even though the evidence is still not incontrovertible, the possibility that the bioactive metabolites found in medical plants may derive from the activity of endophytic microorganisms cannot be excluded; endophytes may promote plant health and growth, elicit plant metabolism, or directly produce biotechnologically relevant compounds (Brader et al, 2014). Moreover, Zhao et al (2010) found that the metabolites derived from the endophytes found in Pichia guilliermondii were potential antimicrobial agents, which confirms our understanding of the relationship between the endophytes and their host. In this context, the characterization of uncultivatable microorganism communities is a fundamental step towards the production of natural antimicrobial agents because it paves the way to understanding the important role played by endophytes in plant metabolism.…”
Section: Resultsmentioning
confidence: 57%
“…Some studies have also reported the isolation of M. caribbica from other sources, such as the digestive tract of Aedes aegypti (Gusmão et al, 2007) and fermented beverages (Papalexandratou and Vuyst, 2011;Hidalgo et al, 2012). M. guilliermondii has also been isolated as an endophytic yeast (Zhao et al, 2010) from bovine milk (Zaragoza et al, 2011) and the genital tract of female camels (Shokri et al, 2010). These species have been cited in literature as producers of xylitol (Rao et al, 2007).…”
Section: Discussionmentioning
confidence: 99%